Gastric Trichobezoars in paediatric population– A series of six cases and literature review. (December 2022) - Habib, Murad; Amjad, Muhammad Bin; Abbas, Muhammad; Chaudhary, Muhammad Amjad
Abstract: Background: Trichobezoar is a rare gastrointestinal pathology in paediatric population. Patients present with a range of symptoms from being asymptomatic to abdominal pain with a palpable abdominal mass. Once diagnosed it warrants urgent retrieval as delayed diagnosis may lead to serious complications. Methods: We present a series of six cases between March 2021 and March 2022 who presented to Children's Hospital and were diagnosed as a case of Gastric Trichobezoars. Patients were optimized and prepared for surgery. All patients underwent Surgical exploration and a tuft of hair were removed. They were followed up throughout the course of treatment and three of the patients underwent psychiatric evaluation. Discussion and conclusion: Trichobezoar is a rare but important surgical case that is a manifestation of underlying psychiatric ailment. Presentation varies from asymptomatic masses to life threatening complications with delayed presentations. A multi-disciplinary approach including Psychiatric, Paediatrician and Paediatric surgeon should be undertaken. Follow-up is the mainstay of treatment and recurrence may be seen due to non-compliance or inadequate management. Highlights: Gastric trichobezoar is extremely rare in paediatric population. Patient presents with non-specific symptoms and can easily be missed. If a diagnosis of Gastric Trichobezoar is made, then it's a surgical emergency. If a Trichobezoar extends beyond pylorus into the small intestine it's called Rapunzel syndrome. Psychiatric evaluation should be done for underlying disorder (trichotillomania).